Online Authentication and Key Establishment Scheme for Heterogeneous Sensor Networks - Sarmad Ullah Khan; Luciano Lavagno; Claudio Pastrone; Maurizio A. Spirito (International Journal of Distributed Sensor Networks)
In recent years, the adaptation of wireless sensor networks (WSNs) to application areas requiring mobility increased the security threats against confidentiality, integrity, and privacy of the information as well as against their connectivity. Since key management plays an important role in securing both information and connectivity, a proper authentication and key management scheme is required in mobility enabled applications where the authentication of a node with the network is a critical issue. In this paper, we present an authentication and key management scheme supporting node mobility in a heterogeneous WSN that consists of several mobile sensor nodes and a few fixed sensor nodes. We analyze our proposed solution by using the OMNET++ simulator to show that it requires less memory space and provides better connectivity and network resilience against node capture attacks compared to some existing schemes. We also propose two levels of secure authentication methods for the mobile sensor nodes for secure authentication and key establishment.